Pengaruh Emic View Terhadap Penetapan Kelayakan Lingkungan Rencana Pembangunan Tenaga Listrik Jawa Bali - Endang Susilowati; Sukriyah Kustanti Moerad; Zaenal Arifin (Institut Teknologi Sepuluh Nopember, 2018)
Based on the official calculation of power supply, the island of Bali requires theincreasing of electric power to support their tourism sectors. The survey'sresults showed that social-environmental feasibility has met the requirementsof Environmental Ministry’s Regulation (no.16, 2012). The assessments of theenvironmental documents, however, did not fulfill one of ten criteria and that isan emic view especially from the religion communities. As a result, the plancould not be done. This paper intends to give an in-depth analysis of howreligion communities try to conceive the governmental planning as a breakingof the religion’s law.